Multiple lump solutions of the (2+1)-dimensional sawada-kotera-like equation - Feng-Hua Qi; Shuang Li; Zhenhuan Li; Pan Wang (Frontiers in Physics, 2022)
In this paper, 1-lump solution and 2-lump solution of a (2 + 1)-dimensional Sawada-Kotera-like equation are obtained by means of the Hirota’s bilinear method and long wave limit method. The propagation orbits, velocities and the collisions among waves are analyzed. By setting the parameter values, the dynamic characteristics of the obtained solutions are shown in 3D and density plots. These conclusions enrich the dynamical theory of higher-dimensional nonlinear dispersive wave equations.